Metafora Kata Mata dalam Bahasa Melayu Riau: Analisis Semantik Kognitif - Hermandra Hermandra (Ranah: Jurnal Kajian Bahasa, 2021)
This study aims to examine the metaphor of the word "eye" in Riau Malay. This research is a qualitative descriptive study using cognitive semantic analysis. The research data was taken from the speech of the Malay community who used the metaphorical expression of the word "eye". The technique used in collecting data is an interview technique assisted by fishing, tapping, and listening to conversational techniques accompanied by recording techniques. Data analysis techniques in the form of data collection, data analysis, and drawing conclusions. The results showed that the use of the word mata can bring up various metaphorical expressions in the language of the Riau Malay community. Practically, the use of the eye can be found in the eye of the basket, knife blade, pineapple eye, hook, fish eye, ring eye, boil eye, panda eye, eye bag, ankle, head eye, and fish eye. The meanings that emerge can be understood and interpreted logically through the life experiences of the Riau Malay community. Experience as a marker that connects the meaning of the expressions conveyed by the Riau Malay community when communicating.AbstrakPenelitian ini bertujuan untuk mengkaji metafora kata “mata” dalam bahasa Melayu Riau. Penelitian ini merupakan penelitian deskriptif kualitatif menggunakan analisis semantik kognitif. Data penelitian diambil dari tuturan masyarakat Melayu yang banyak menggunakan ungkapan metafora kata “mata”. Teknik yang digunakan dalam mengumpulkan data adalah teknik wawancara yang dibantu dengan teknik pancing, sadap, dan simak libat cakap yang disertai dengan teknik rekam. Teknik analisis data berupa pengumpulan data, analisis data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa penggunaan kata mata dapat memunculkan berbagai ungkapan metafora dalam berbahasa masyarakat Melayu Riau. Secara secara praktis, penggunaan mata dapat ditemukan pada mata telanjang, mata pisau, mata nanas, mata kail, mata ikan, mata cincin, mata bisul, mata panda, kantong mata, mata kaki, mata kepala, dan mata ikan. Makna yang muncul dapat dipahami dan diinterpretasi secara logika melalui pengalaman hidup masyarakat Melayu Riau. Pengalaman sebagai penanda yang menjadi penghubung maksud dari ungkapan yang disampaikan masyarakat Melayu Riau saat berkomunikasi.